"Create in Me a Clean Heart": The Role of Spirituality in Desistance From Substance Use. (April 2019) - Crank, Beverly Reece; Teasdale, Brent
Although the impact of religion on behavior is robust and well-examined in many areas, the role spirituality plays in changes in drug use over time has received relatively little attention. Using a life-course theoretical framework, this relationship is examined through growth curve modeling techniques. Specifically, multilevel analyses are estimated testing within-person relationships between substance use desistance and spirituality. The Pathways to Desistance longitudinal data are analyzed and leading criminological predictors are included, to determine if spirituality has a unique impact on substance use net of these criminological factors, and if these impacts vary across gender. Results from these analyses suggest that the impact of spirituality on desistance varies by gender, with spirituality significantly increasing the odds of desistance from marijuana use for females, but not males.